The negative impact of poor health on civic participation in older adults of the Baltic countries - Mikulionienė Sarmitė (SHS Web of Conferences, 2024)
Civic participation as a specific subtype of social participation in later life has received little attention from researchers. How to maintain the well-being and health of older adults through their involvement in the community is crucial to understand the prevalence of civic participation in older age, especially for those in poor health. This study fills the gap in knowledge on the relationship between the civic participation of older adults in the Baltics and their health status. The data come from a quantitative survey of Lithuania, Latvia, and Estonia’s residents aged 50 years and older (N = 2015) conducted in 2019-2020. Data were analysed based on Serratet et al. [1] concept of civic activity and health status, using descriptive statistics and multinomial regression analysis. The results show that the profile of civic participation people aged 50+ is asymmetrical: 1) individual rather than collective and social rather than political participation is prevalent, and 2) poor health limits the participation of older adults in almost every civic activity (especially those that are more resource-intensive). The research results can be helpful for social policymakers and practitioners (social workers).